2018
DOI: 10.1021/acs.macromol.7b02244
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Weak Polyelectrolyte Brushes in Mixed Salt Solutions

Abstract: Hydrophilic and hydrophobic weak polybasic brushes immersed in aqueous solutions of mixed salt counterions are considered using a mean-field numerical self-consistent field approach. On top of the solvent quality of the polymer, the counterion–solvent interactions are accounted for by implementing Flory–Huggins interaction parameters. We show that ion specificity within the brush can bring about large changes in conformation. It is found that the collapse transition of hydrophobic, weak polyelectrolyte brushes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…To our knowledge, few reports addressed the specific ion effects in salt mixtures [88,[236][237][238][239][240][241][242][243][244]. For example, Bastos-Gonzales et al investigated the electrophoretic mobility of charged PNIPAM particles in 10 mM Na2SO4, 10 mM NaSCN, and a 5 mM + 5 mM mixture of both [183].…”
Section: Specific Ion Effects In Salt Mixtures: Additivity Vs Non-additivitymentioning
confidence: 99%
“…To our knowledge, few reports addressed the specific ion effects in salt mixtures [88,[236][237][238][239][240][241][242][243][244]. For example, Bastos-Gonzales et al investigated the electrophoretic mobility of charged PNIPAM particles in 10 mM Na2SO4, 10 mM NaSCN, and a 5 mM + 5 mM mixture of both [183].…”
Section: Specific Ion Effects In Salt Mixtures: Additivity Vs Non-additivitymentioning
confidence: 99%
“…As well as their role in underwater adhesives and encapsulation [21,23,24]. Extensive studies on the effects of counterions in determining the assembly and stability of polyelectrolyte complexes have been performed by several groups [25,26,27,28,29,30,31,32,33], though these have largely ignored the role of solution acidity in determining the charge on these compounds, which is crucial for dense polyelectrolyte assemblies [28,34,35,36,37,38]. Importantly, it was recently shown that the pH could significantly alter the charging equilibrium, and indeed the underlying thermodynamics of the process, when acidity and salinity are explicitly accounted for [33].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging applications of weak polyelectrolytes in smart materials demand sensitive response, with systems balanced on a knife’s edge ready to adapt their microstructure precisely in response to the local stimuli, it is imperative that we be able to accurately understand the structure of weak polyelectrolytes across a wide range of acidity and salinity. While some theoretical work has been performed in the area of weak polyelectrolyte brushes [36,37,59,60,61], computer simulations, which often utilize simplified, coarse-grained models to extract essential trends and behavior, represent an ideal place to deepen understanding and develop intuitions for weak polyelectrolyte materials. For instance, simulations have been performed to elucidate the ionization of weak polyelectrolytes in non-aqueous environments [58], where it was found that ionization of weak polyelectrolytes may be enhanced by an increase of the electrostatic coupling constant Γ=λB/σ (where λnormalB is the Bjerrum length and σ the size of monomers—see Section 2 for further discussion) due to energetically favorable interactions between a dissociated ion and monomer pair.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have used mean-field theory to make predictions about the behavior of weak polyelectrolyte brushes in solutions containing mixtures of salts (mixed salt solutions). 30 For hydrophilic polymers, the influence of mixed salts is predicted to be small. However, the effects predicted for hydrophobic polymers are much more dramatic.…”
Section: Introductionmentioning
confidence: 99%